Case Report: Neuroblastoma-Like Schwannoma in a Domestic Short-Haired Cat - Vivian S. Chen; Andrew W. Bollen; Paola Marco-Salazar; Robert J. Higgins; Sílvia Sisó; Sílvia Sisó (Frontiers in Veterinary Science, 2022)
An axillary mass was detected in a 6-year-old, neutered, male, domestic short-haired cat during a wellness exam. Gross examination following surgical removal revealed a discrete, deep subcutaneous, discoid mass that was between 0.5- and 0.7-cm-in-diameter and diffusely firm and white. Histologically, the mass was well-demarcated, partially encapsulated, and expanded the panniculus carnosus. It was composed of tightly packed, giant rosettes of radially arranged fusiform cells stacked in one to 10 layers with peripherally palisading nuclei and with centrally oriented, fibrillary, cytoplasmic processes, and collagenous fibers. Laminin immunoreactivity and ultrastructural examination highlighted a continuous basal lamina outside the plasma membrane of each neoplastic cell. Neoplastic cells were immunoreactive for GFAP, S100, periaxin, and Sox-10 and were immunonegative for synaptophysin, smooth muscle actin, and pancytokeratin. Collective findings were consistent with a diagnosis of neuroblastoma-like schwannoma. This is the first veterinary report of this rare variant of benign schwannoma.